srpski - srpski, srpski; Olujić, Biljana (Medical Gazzette, 2026)
Graves’ orbitopathy (GO), the most common extrathyroidal manifestation of autoimmune hyperthyroidism, typically occurs within the first year after diagnosis, although it may rarely develop in euthyroid and hypothyroid patients as well. Following total thyroidectomy, GO may develop in approximately 10–20% of patients, symptoms usually appear several months to one year after surgery. The risk is higher in patients with elevated thyrotropin receptor antibodies (TRAb), smokers, and patients who do not initiate levothyroxine replacement therapy promptly. Intravenous corticosteroid therapy represents the first-line treatment. A 69-year-old female patient with autoimmune thyroid disease initially presented with autoimmune hyperthyroidism and received antithyroid drug therapy for five years without developing orbitopathy during treatment. Failure to achieve sustained disease control, second-line treatment was implemented, and total thyroidectomy was performed, resulting in hypothyroidism and hypoparathyroidism. Subsequently, she was adequately substituted with levothyroxine, alfacalcidol, and calcium supplementation. The patient also underwent surgery for colon adenocarcinoma and received chemotherapy postoperatively. Nine years after thyroidectomy, despite regular vaccination, she developed COVID-19 infection and was treated with biologic therapy consisting of a monoclonal antibody targeting the SARS-CoV-2 spike protein, together with antiviral treatment. Eleven years after total thyroidectomy, the patient developed moderate-to-severe GO with moderate clinical activity, intermittent diplopia, and elevated TRAb levels. Intravenous corticosteroids resulted in a satisfactory therapeutic response. The occurrence of GO, as the most common extrathyroidal manifestation of autoimmune hyperthyroidism, is exceptionally rare several years after the onset of hyperthyroidism and even more uncommon following surgical treatment of autoimmune hyperthyroidism. COVID-19 infection, biologic therapy, and coexisting comorbidities may have acted as potential triggers for reactivation of autoimmune processes in this patient.